Antenna control systems from PI to H∞. - Gawronski, Wodek (IEEE Antennas & propagation magazine.)
This paper discusses the compensation of antenna-pointing errors following the analysis and retrofit of the NASA Deep Space Network antenna control systems. The desired high-frequency communications with spacecraft (at Ka-band) require improved pointing precision over lower-frequency communications (at X-band). The quality of the antenna drives (hardware), the control algorithm (software), and the physical structure of the antenna (in terms of thermal deformations, gravity distortions, encoder mounting, and wind gusts) all influence pointing precision, and create the challenging task of remaining within the required pointing-error budget. Three control algorithms-PI (proportional-and-integral), LQG (linear-quadratic-Gaussian), and H∞-are discussed, and their basic properties, tracking precision, and limitations as applied to antenna tracking are addressed. The paper shows that the PI algorithm is simple and reliable, but its performance is limited. It also explains how significant improvements in tracking precision are achieved when implementing the LQG control algorithm or the H∞ control algorithm. Still, pointing precision attributable to software modification is limited. It is pointed out that an additional increase of tracking precision requires concurrent improvements in the antenna drives.